Remarks by Mark Ward. (2021) - Ward, Mark
Abstract : I am a former lawyer and retired American diplomat and currently country director of a large humanitarian organization working in Afghanistan. As I explained during the panel, the International Medical Corps is faced with the challenges of delivering humanitarian assistance in the middle of a twenty-year armed conflict. We must stay true to humanitarian principles, like neutrality, but avoid donor governments' concerns that we not engage too much with their enemy, the Taliban.